Venous effects of oral contraceptives - Grant, Ellen C. G. (1969)
In a five-year analysis of an oral contraceptive trial by the Council for the Investigation of Fertility Control venous effects were the third most troublesome group of side-effects with both combined and sequential therapy. Vein complaints, leg cramps, and thrombophlebitis were significantly more frequent with the combined preparations that contained a relatively low dose of progestogen and a high dose of oestrogen than with the other groups tested. No cases of thrombophlebitis occurred in women taking the strongly oestrogenic sequential groups. Histological examination of uterine curettings showed that most progestogenic combined preparations were associated with a high incidence of dilated endometrial sinusoids, while the oestrogenic sequential regimens and low-dose progestogen-only regimens had a low incidence. The incidence of stromal condensation round the sinusoids correlated with the incidence of leg cramps, and these effects appeared to be specific for each preparation tested.